SAT0102 Stem Cell Augmentation for Cardiovascular Risk in Rheumatoid Arthritis with Olmesartan: Star-O Study. (9th June 2015) - Syngle, A.; Garg, N.; Krishan, P.
Abstract : Background: Cardiovascular disease remains the leading cause of mortality in rheumatoid arthritis (RA). Endothelial progenitor cells (EPCs) are depleted and contribute to increased cardiovascular (CV) risk in RA. 1 Olmesartan exerts a protective cardiovascular effect in diabetes by augmenting EPCs. 2 However, this vasculoprotective effect of olmesartan has not yet been investigated in RA. Objectives: To investigate the impact of olmesartan on circulating endothelial progenitor cell population in RA. Methods: Forty RA patients fulfilling the 2010 Rheumatoid Arthritis classification criteria were randomized to receive 24 weeks of treatment with olmesartan (10mg/day, n=20) or placebo (n=20) as an adjunct to existing stable antirheumatic drugs. EPCs (CD34 + /CD133 + ) were quantified by Flow cytometry. Flow mediated dilatation (FMD) was assessed by AngioDefender™ (Everest Genomic Ann Arbor, United States). Inflammatory measures included DAS28, CRP, ESR, pro-inflammatory cytokines (TNF-α, IL-6 and IL-1), serum nitrite and adhesion molecules (ICAM-1 and VCAM-1) at baseline and after 24 weeks treatment. Results: At baseline, inflammatory measures, pro-inflammatory cytokines, adhesion molecules and nitrite levels were elevated and EPCs and endothelial function were impaired among both groups. EPCs significantly 0.018±0.001 to 0.031±0.001 increased p<0.01 after treatment with olmesartan but did not show significant change with placebo 0.019±0.001 to 0.022±0.001, p=0.14. After 24 weeks of treatment, FMD improved significantly from (5.2±1.4 to 9.0±1.10, p=0.01) as compared to placebo (p=0.47) group. Olmesartan significantly decreased systolic/diastolic blood pressure (mean difference, -7.5/-1.6, p=0.01) as compared with placebo (mean difference, -4.1/-1.2, p>0.05). After 24 weeks: inflammatory measures DAS28, ESR, CRP (All p=0.01) and nitrite (p=0.03) were significantly reduced after treatment with olmesartan. Proinflammatory cytokines TNF-α, IL-6 and VCAM-1 significantly (p=0.38, p=0.02 and 0.01 respectively) reduced in olmesartan group. Significant negative correlation was observed between EPCs and CRP (Fig. 1A ), TNF- α (Fig. 1B ), IL-6, VCAM-1 (Fig. 1D ) and FMD (Fig. 1C ) after treatment with olmesartan. Conclusions: First study to show that olmesartan improves inflammation, EPC biology and endothelial dysfunction in RA possibly through its anti-inflammatory effect via inhibition of proinflammatory cytokines. This anti-inflammatory effect may be of therapeutic relevance in RA. References: Grisar J et al. Circulation. 2005;111:204-211. Bahlmann FH et al. Hypertension. 2005;45:526-29 Acknowledgements: This study was supported by Research Grant from Universal Grant Commission, New Delhi [F. No.41-725/2012 (SR)]. Disclosure of Interest: None declared